Irrigation institutions in a dynamic economy: What is China doing differently from India? - Shah, Tushaar; Giordano, Mark; Wang, Jinxia (2004)
India's water sector is crying for institutional and policy reforms. Its public irrigation systems are performing far below par. As a direct consequence, farmers are turning to groundwater for their irrigation needs. Booming groundwater irrigation has become the mainstay of Indian farming but it has also all but wrecked the country's power economy because of perverse policies of pricing of electricity for agriculture. Yet, there is no firm strategy of dealing with these and other challenges. Other south Asian countries are in much the same boat. Based on two spells of fieldwork in six provinces of north China, this article shows that, facing much the same problems as its south Asian neighbours, China is responding differently to its water problems. This is by no means a suggestion that the approaches China is trying out would work in India - or even in China itself. However, by including China's experience in its discussions, Indian policy-makers will clearly have a wider repertoire of institutional alternatives with which to experiment.